PENINGKATAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI MENGGUNAKAN METODE FIELD TRIP PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SD NEGERI DADAPSARI - Kholifaturrahmah Kholifaturrahmah; Amaliyah Ulfah (Universitas Ahmad Dahlan, 2018)
Teacher teaching methods that are less varied in Indonesian language learning cause, the low value of the ability to write student description essays. The purpose of this study was to improve the ability to write a description essay using the field trip method for fourth grade students of SD Negeri Dadapsari Sleman. This research is a Classroom Action research, with 2 cycles of action. The subjects in this study were the fourth grade students of SD Negeri Dadapsari which numbered 20 students, while the objects in this study were the ability to write a description essay. Data collection techniques were in the form of observation, tests and documentation. The research instrument consisted of observation sheets and essay test sheets. The analysis technique used is descriptive and quantitative data analysis. The results showed that field trip methods can improve the ability to write description essays. This is confirmed by; 1) Field trip methods have been shown to increase student enthusiasm and student activity, with the material provided and supported by the environment making students curiosity emerge. 2) From the results of the study it can be shown that there is an increase in the ability to write description essays, namely an increase in the first cycle of the first meeting, there are 5 students with a percentage (25%), then increasing in the second meeting there are 8 students with a percentage (40%) who obtain complete grades. While the results of the ability to write an essay description in the second cycle of the first meeting there were 14 students with a percentage (70%) who got the complete score, for the second meeting there were 18 students with a percentage (90%) of students who received complete grades. The results of the percentage show that the ability to write student description essays can be increased by applying the field trip method.